Influence Of Determinant Factors On Report Quality Nagekeo District Skpd Finance - Beka Yuju, Susana Clarica; Ekaningtias, Diah (FAKULTAS EKONOMI UNIVERSITAS MAARIF HASYIM LATIF, 2023)
This study aims to determine the effect of Accounting Information Systems, Government Accounting Standards, Organizational Culture, and Internal Control Systems on the quality of SKPD financial reports in Nagekeo Regency. In this study, the population used was SKPD employees in Nagekeo Regency, and the sample for this study was 74 employees in the finance department—the selection of pieces was based on the purposive sampling technique. The data collected is primary data obtained from distributing questionnaires. The analytical method used uses the outer model and inner model. For data analysis, they were tested using SmartPLS 4.0. The results of this study indicate that the Accounting Information System has an effect on the Quality of SKPD Financial Reports in Nagekeo Regency, Government Accounting Standards have no effect on the Quality of SKPD Financial Reports in Nagekeo Regency, Organizational Culture has no impact on the Quality of SKPD Financial Reports in Nagekeo Regency, and the Internal Control System has an effect on Report Quality SKPD Finance of Nagekeo Regency.